2015
DOI: 10.1007/s11250-015-0848-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of H9N2 avian influenza viruses isolated from vaccinated broiler chickens in northeast Iran

Abstract: Avian influenza is a highly contagious respiratory disease of poultry caused by influenza A viruses, family Orthomyxoviridae. H9N2 avian influenza outbreaks are a major problem of the poultry industry in Iran. To determine the genetic differences between field viruses and the vaccine strain, the genomes of four strains isolated in 2011 from vaccinated broiler flocks with a history of respiratory illness were sequenced. Genetic and serological comparisons were made. Sequence analysis of the hemagglutinin (HA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Mutations in the HA glycoprotein are known to be particularly influential on modulating the overlapping and interrelated properties of receptor specificity, host and tissue tropism, pathogenicity, and antigenicity (32, 43, 50). Conventional avian influenza vaccines typically lose efficacy as HAs undergo antigenic drift, and several research groups have suggested that the widespread use of poultry vaccines may even contribute to driving antigenic drift (21, 22, 24, 51, 52). Recently, we generated a panel of “antigenic drift-like” escape mutants (through in vitro selection with MAbs), some of which contained deletions within the 220 loop region of the HA RBS (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in the HA glycoprotein are known to be particularly influential on modulating the overlapping and interrelated properties of receptor specificity, host and tissue tropism, pathogenicity, and antigenicity (32, 43, 50). Conventional avian influenza vaccines typically lose efficacy as HAs undergo antigenic drift, and several research groups have suggested that the widespread use of poultry vaccines may even contribute to driving antigenic drift (21, 22, 24, 51, 52). Recently, we generated a panel of “antigenic drift-like” escape mutants (through in vitro selection with MAbs), some of which contained deletions within the 220 loop region of the HA RBS (34).…”
Section: Discussionmentioning
confidence: 99%
“…Classical inactivated vaccines have been widely utilized in poultry in many areas to attempt to curb economic losses associated with H9N2 infection (8, 2124). Veterinary influenza vaccines face challenges similar to those of human seasonal influenza vaccines in terms of requiring continual evaluation and updating due to virus antigenic drift.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the economic damage caused by enzootic H9N2, many countries including China, Israel, South Korea, Morocco, Pakistan, Egypt and Iran have adopted vaccination at either a national or local level as a key approach for preventing H9N2 disease in poultry [28,36,44,[178][179][180][181].…”
Section: Vaccination and Controlmentioning
confidence: 99%
“…Therefore, in many regions H9N2 viruses continue to infect and cause disease in vaccinated poultry with tentative evidence suggesting that sub-optimal use of vaccination may be driving antigenic drift and/or clade replacement, and theoretically zoonotic potential and pathogenesis [27,28,41,73,86,181,182]. Because of this there is a real need for i) better understanding of the molecular determinants of H9 antigenicity, ii) better understanding of antigenic drift and the consequences upon viral fitness and zoonotic potential and iii) next generation vaccines that protect better against multiple strains and antigenically drifted variants.…”
Section: Vaccination and Controlmentioning
confidence: 99%